Identification of MltG as a Prc Protease Substrate Whose Dysregulation Contributes to the Conditional Growth Defect of Prc-Deficient Escherichia coli - Hsu, Po-Chuen; Chen, Chien-Sheng; Wang, Shuying; Hashimoto, Masayuki; Huang, Wen-Chun; Teng, Ching-Hao (Frontiers in Microbiology, 2020)
Microbial proteases play pivotal roles in many aspects of bacterial physiological processes. Because a protease exerts its biological function by proteolytically regulating its substrates, the identification and characterization of the physiological substrates of a protease advance our understanding of the biological roles of the protease. Prc (also named Tsp) is an Escherichia coli periplasmic protease thought to be indispensable for E. coli to survive under low osmolality at 42°C. The accumulation of the Prc substrate MepS due to Prc deficiency contributes to the conditional growth defect. Because preventing MepS accumulation only partially restored the growth of Prc-deficient E. coli, we hypothesized that other unidentified Prc substrates intracellularly accumulate due to Prc deficiency and contribute to the conditional growth defect. To identify previously undiscovered substrates, 85 E. coli proteins able to physically interact with Prc were identified using E. coli proteome arrays. Ten proteins were shown to be cleavable by Prc in vitro. Among these candidates, MltG was able to interact with Prc in E. coli. Prc regulated the intracellular level of MltG, indicating that MltG is a physiological substrate of Prc. Prc deficiency induced the accumulation of MltG in the bacteria. Blocking MltG accumulation by deleting mltG partially restored the growth of Prc-deficient E. coli. In addition, Prc-deficient E. coli with blocked MltG and MepS expression exhibited higher growth levels than those with only the MltG or MepS expression blocked under low osmolality at 42°C, suggesting that these accumulated substrates additively contributed to the conditional growth defect. MltG is a lytic transglycosylase involved in the biogenesis of peptidoglycan (PG). In addition to MltG, the previously identified physiological Prc substrates MepS and PBP3 are involved in PG biogenesis, suggesting a potential role of Prc in regulating PG biogenesis.